Drawing with Ink as an Enjoyable and Creative Activity for Children - Wardoyo, Bambang Tri; Hambawan, Tulus; Nasir, Roziani Binti Mat Nashir @ Mohd; Setiadi, Virginia Suryani; Utomo, R. Drajatno Widi; Murwonugroho, Wegig (Unram Journal of Community Service, 2025)
Drawing training for children is an enjoyable and creative activity, yet it is often overlooked in today's digital era. This background issue arises from the fact that many children prefer to play with gadgets rather than engage in artistic activities that can enhance their motor skills and creativity. The objective of this training is to provide a fun and educational drawing experience, allowing children to express themselves through abstract art and color exploration. The training methods employed include a free and unstructured approach, color games, and emotion & imagination-based activities, which encourage children to create without limitations. The conclusion of this training indicates that drawing activities not only improve children's artistic skills but also awaken their aesthetic sensitivity and motor creativity, making art an essential medium for holistic development amidst the challenges of the modern world.